Ref-1 redox activity modulates canonical Wnt signaling in endothelial cells - Gabriella D. Hartman; Kamakshi Sishtla; Eyram K. Kpenu; Mahmut Mijit; Anbukkarasi Muniyandi; Ha-Neul Jo; Harald J. Junge; Aaron Shaw; Daniela Bischof; Sheng Liu; Jun Wan; Mark R. Kelley; et al. (Redox Biology)
Ischemic retinopathies, including proliferative diabetic retinopathy (PDR) and retinopathy of prematurity (ROP), are characterized by abnormal retinal neovascularization and can lead to blindness in children and adults. Current treatments, such as intravitreal anti-VEGF injections, face limitations due to high treatment burden and variable efficacy, as multiple signaling pathways, beyond VEGF, contribute to retinal neovascularization. Previous studies demonstrate that targeting the redox-mediated transcriptional regulatory function of APE1/Ref-1 reduces pathological neovascularization. We aimed to identify novel signaling pathways regulated by Ref-1 redox activity utilizing RNA sequencing of human retinal endothelial cells (HRECs) treated with a Ref-1 redox inhibitor. We found that Wnt/β-catenin signaling was significantly downregulated after Ref-1 inhibition. Given the role of Wnt signaling in vascular pathologies, we investigated how Ref-1 regulates Wnt/β-catenin signaling. Ref-1 inhibition downregulated Wnt co-receptors LRP5/6 at both the mRNA and protein levels in endothelial cells, suggesting transcriptional regulation. Ref-1 redox inhibitors APX3330 and APX2009 reduced Wnt3a-induced nuclear β-catenin levels, decreased Wnt transcriptional activity by TOPFlash luciferase assay, and blocked hypoxia-induced Wnt/β-catenin activation in HRECs. In the oxygen-induced retinopathy mouse model of retinal neovascularization, Ref-1 specific inhibitor APX2009 reduced the expression of Wnt-related genes at sites of neovascularization. These findings reveal a novel role for Ref-1 redox activity in modulating Wnt/β-catenin signaling in endothelial cells and highlight the potential of Ref-1 redox activity targeted inhibitors as a novel therapeutic approach for retinal neovascular diseases by modulating multiple disease-relevant pathways.